2012
DOI: 10.3109/02688697.2012.732715
|View full text |Cite
|
Sign up to set email alerts
|

Does rectal examination have any value in the clinical diagnosis of cauda equina syndrome?

Abstract: Digital rectal examination has no significant value in the acute diagnosis of cauda equina syndrome. This study further confirms that there is no discreet clinical protocol applicable with which to confidently confirm or rule out this diagnosis. DRE is traditionally enshrined as an essential facet of clinical assessment in suspected cauda equina syndrome but it cannot be used as a discriminator to ration urgent MRI scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 21 publications
3
29
2
Order By: Relevance
“…This study displays unique data on the presenting symptoms of a large group of CES patients, proving that, next to the well-acknowledged micturition dysfunction, also defecation and sexual dysfunction are common at presentation. Anal sphincter tension and anal sphincter reflex are often tested in CES patients, even though several studies found no diagnostic value for these tests [18][19][20][21]. In the current study, abnormal anal sphincter reflex was not significantly associated with any of the diagnostic criteria for CES used in this study (closest to an association was defecation dysfunction with p = 0.096).…”
Section: Discussioncontrasting
confidence: 60%
“…This study displays unique data on the presenting symptoms of a large group of CES patients, proving that, next to the well-acknowledged micturition dysfunction, also defecation and sexual dysfunction are common at presentation. Anal sphincter tension and anal sphincter reflex are often tested in CES patients, even though several studies found no diagnostic value for these tests [18][19][20][21]. In the current study, abnormal anal sphincter reflex was not significantly associated with any of the diagnostic criteria for CES used in this study (closest to an association was defecation dysfunction with p = 0.096).…”
Section: Discussioncontrasting
confidence: 60%
“…Back pain and radicular leg pain are the most common presentations of CES, although the classic teaching is that of perineal paresthesias and bowel and bladder changes [20,21]. However, these are commonly found in the later stages of CES.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with CES due to LDH have a history of LDH, and the percentage was reported as 70%-82% (4, 5, 8). Gooding et al (6) suggested that CES can be seen in only 0.12% of patients with LDH. Additionally, it was reported that 1%-2% cases of LDH may cause CES (7).…”
Section: Discussionmentioning
confidence: 99%